1975
DOI: 10.1007/bf00238732
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological studies of the projections from the parietal association area to the cerebellar cortex

Abstract: 1. Responses evoked in the cerebellar cortex by stimulation of the parietal association cortex (rostral portions of the middle suprasylvian gyrus) were recorded and analysed in cats, and were compared with those by stimulation of the motor cortex (anterior sigmoid gyrus). 2. The parietal stimulation elicited early mossy fibre and late climbing fibre responses in the cerebellar cortex. The mossy fibre responses appeared at a latency of 2.0--2.5 msec and predominantly in the lateral (hemispherical) part of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 21 publications
5
45
0
Order By: Relevance
“…Thus, degree of complex spike synchrony itself may also be modulated by sensory stimulus during the awake state. Extensive projections are known to exist from motor and association areas of the cerebral cortex to the lateral cerebellum (Sasaki et al, 1975), the region we examined in the present study. It is therefore possible that electrotonic coupling between neuronal ensembles in the inferior olive are modulated by inputs from the cerebral cortex depending on vigilance or behavioral state of the animal.…”
Section: Microzones Can Be Reorganized and Coordinated During Awake Smentioning
confidence: 99%
“…Thus, degree of complex spike synchrony itself may also be modulated by sensory stimulus during the awake state. Extensive projections are known to exist from motor and association areas of the cerebral cortex to the lateral cerebellum (Sasaki et al, 1975), the region we examined in the present study. It is therefore possible that electrotonic coupling between neuronal ensembles in the inferior olive are modulated by inputs from the cerebral cortex depending on vigilance or behavioral state of the animal.…”
Section: Microzones Can Be Reorganized and Coordinated During Awake Smentioning
confidence: 99%
“…Electrophysiological studies have demonstrated that excitatory responses of the olivocerebellar system can be evoked from areas throughout the neuraxis (Provini et al, 1968;Allen et al, 1974;Oscarsson and Sjölund, 1974;Sasaki et al, 1975Sasaki et al, , 1977Jeneskog, 1981aJeneskog, ,b, 1987. Immunohistochemical studies have provided evidence of glutamate receptor subunits throughout the IO (Petralia and Wenthold, 1992;Ambalavanar et al, 1998;Paarmann et al, 2000), suggesting that these excitatory responses could be mediated by glutamate.…”
Section: Glutamate Receptors Mediate Excitatory Drive To the Inferiormentioning
confidence: 99%
“…The latencies of the CF responses evoked by stimulation of the frontal cortex, parietal cortex and AESv were 12-16, 17-19 and 14-17 ms, respectively (Sasaki et al 1975;Oka et al 1979). The CF responses to AESv stimulation were as stable from trial to trial as those evoked by stimulation of the frontal cortex.…”
Section: Indirect Cerebro-olivary Projectionmentioning
confidence: 79%
“…Sasaki and his colleagues showed that there is a reciprocal connection between the parietal cortex and the lateral part of the cerebellum. Specifically, they found that the cerebellar lateral nucleus projects to the parietal cortex (Sasaki et al 1972) and that the parietal cortex projects to the lateral part of the cerebellar cortex (Sasaki et al 1975). These reciprocal connections are considered to be indispensable for performing skilful and co-ordinated movements (Sasaki, 1979).…”
Section: Functional Significance Of the Projectionmentioning
confidence: 99%
See 1 more Smart Citation